Teen esteem : a self-direction manual for young adults - Palmer, Pat, 1928- (Impact Publishers, 1989)
Provides guidance on developing self-esteem and the positive attitude necessary to cope with such adolescent challenges as peer pressure, substance abuse, and sexual expression.